COMPARATIVE STUDY OF MOTHER'S HEALTH BEHAVIORS IN HOSPITALIZED INFANTS WITH DIARRHEA OR WITHOUT IT - Raftari, Z; Tavakoli, M.A; Zarrin Naal, A (Iran University of Medical Sciences, 2003)
Background: Although, many efforts have been carried out regarding infant ' s health in recent years, consistent infections such as diarrhea is a cause of pathogenecity or even death among infants under 2 years old according to not have done which is attributed to inadequate nutrition and health care.   Objective: To compare mother ' s health behaviors in hospitalized infants with diarrhea or without it, in pediatric department of Ali- Ebn- Abitaleb hospital.   Design: This was a descriptive study. For gathering information, check lists were used.   Sample: 434 mothers of infants which were under the age of two contributed in this study.   Result: There was just a significant difference between infants nutritional status and the cause of admission ( P=0.0002), in that, breast fed babies had the lower occurrence of diarrhea, in comparison with those who were not. No significant relationship was found between sex and the cause of admission, but the number of boys suffering from diarrhea was more than the girls.   Conclusion: Regarding the findings, as breast feeding, in comparison to animal or industrial milk, decrease the risks of diarrhea, it is recommended to breast fed babies till the end of age two. Which will inhibit the risk of diarrhea and it ' s complications.